Fatores determinantes do nível de recursos internos nos municípios brasileiros - Lira, Aluska Ramos de (2019)
The analysis of municipal financial equilibrium is important to identify the capacity of local governments to offer and maintain the continuity of goods and services to society, as well as to anticipate financial tensions, preventing the crisis from settling. In this sense, it seeks to control financial equilibrium and prevent collapse by maintaining sufficient levels of internal resources to meet its current obligations. Thus, this research aimed to identify the determinant factors of the level of internal resources of the Brazilian municipalities in the period from 2007 to 2017. The analysis undertaken was composed by all Brazilian municipalities, being adopted as a research method a linear regression model using fixed-effects panel data. The results indicated that among the determinant factors of the level of internal resources in Brazilian municipalities are the dependence on fiscal transfer, the level of unemployment associated with a high degree of dependent population, the level of indebtedness of the entities in the face of the need to make financial contributions to amortize the contracted debts that negatively have impacted the level of internal resources of the municipalities. In a transversal way, it was evidenced that the indebtedness has a statistical relationship with the economic crisis, which affects more directly the levels of internal resources. Finally, the factors that have a positive influence on the level of internal resources were the population's income, the educational level of the population that produces higher levels of labor force and, consequently, enhances the levels of internal resources through the capacity of the government in obtaining its own revenues. Electoral and crisis periods alone were not statistically significant in the empirical model of the research.